Composition and sources of winter haze in the Bakken oil and gas extraction region. (May 2017) - Evanoski-Cole, A.R.; Gebhart, K.A.; Sive, B.C.; Zhou, Y.; Capps, S.L.; Day, D.E.; Prenni, A.J.; Schurman, M.I.; Sullivan, A.P.; Li, Y.; Hand, J.L.; Schichtel, B.A.; et al.
Abstract: In the past decade increased use of hydraulic fracturing and horizontal drilling has dramatically expanded oil and gas production in the Bakken formation region. Long term monitoring sites have indicated an increase in wintertime aerosol nitrate and sulfate in this region from particulate matter (PM2.5 ) measurements collected between 2000 and 2010. No previous intensive air quality field campaign has been conducted in this region to assess impacts from oil and gas development on regional fine particle concentrations. The research presented here investigates wintertime PM2.5 concentrations and composition as part of the Bakken Air Quality Study (BAQS). Measurements from BAQS took place over two wintertime sampling periods at multiple sites in the United States portion of the Bakken formation and show regionally elevated episodes of PM2.5 during both study periods. Ammonium nitrate was a major contributor to haze episodes. Periods of air stagnation or recirculation were associated with rapid increases in PM2.5 concentrations. Volatile organic compound (VOC) signatures suggest that air masses during these episodes were dominated by emissions from the Bakken region itself. Formation rates of alkyl nitrates from alkanes revealed an air mass aging timescale of typically less than a day for periods with elevated PM2.5 . A thermodynamic inorganic aerosol model (ISORROPIA) was used to investigate gas-particle partitioning and to examine the sensitivity of PM2.5 concentrations to aerosol precursor concentrations. Formation of ammonium nitrate, the dominant component, was most sensitive to ammonia concentrations during winter and to nitric acid concentrations during early spring when ammonia availability increases. The availability of excess ammonia suggests capacity for further ammonium nitrate formation if nitrogen oxide emissions increase in the future and lead to additional secondary formation of nitric acid. Graphical abstract: Highlights: Measured wintertime aerosol and aerosol precursors in National Parks. Discovered regionally elevated PM2.5 concentrations in the Bakken region. High PM2.5 concentrations associated with air mass stagnation or recirculation. VOC measurements link elevated PM2.5 concentrations to oil and gas activities.